Silagens de rações completas a base de palma forrageira sobre o perfil fermentativo, diversidade taxonômica, produção, composição do leite e avaliação econômica de cabras em lactação - Santos, Francisco Naysson de Sousa (2021)
The first aimed to evaluate the productive and morphometric characteristics of forage cactus and gliricídia intercropped at different spacings. The experimental design was in randomized blocks with 4 treatments and 6 replications. The treatments consisted of four spacings between rows, in the planting of gliricídia: E1 (1.0 m), E2 (1.50 m), E3 (2.0 m) and E4 (3.0 m), with 2, 30 m between plants. In the palm, the height, width, total number of cladodes in the plant, length of cladodes, cladode width, total cladode area were analyzed, green and dry matter production, rain use efficiency. There was a significant difference only for plant height and plant width, with increasing linear effect (P<0.05), for forage cactus during two evaluation cycles. The gliricídia in the first year of intercropping, the variables, planar width, number of leaves, weight of branches, green matter and plant dry matter presented differences (P<0.05) in the spacings. The gliricídia can be used in intercropping with the forage cactus at a spacing of 1.0 m since, in addition to not compromising the performance and production of green matter of the two crops, it increases the efficiency of the use of the area. In the second and third experimental trial, the objective was to evaluate the effects of forage cactus levels in complete feed silages on the fermentation profile, microbial populations, aerobic stability, taxonomic diversity, silage losses and in situ degradability of dry matter. The design used was completely randomized, in a 4x4 factorial arrangement with six replications, four rations with different proportions of forage cactus (15; 30; 45 and 60% based on natural matter) and four silo opening periods (0, 15, 30 and 60 days of fermentation). An interaction effect (P<0.05) was observed between the rations and the opening time for mold and yeast population. A significant difference was observed for the richness and diversity index (P<0.05) (Chao1 and Shannon test). The most abundant bacterial phyla were Proteobacteria and Firmicutes and the genera Lactobacillus and Weissella. Gas losses were minimal and without differences between treatments (P>0.05), remaining below 1% in all complete feed silages in the study. In addition, effluent losses were not significantly different (P>0.05) between the silages, with an average of 13.6 kg tol-1 being observed. Forage cactus can be included in complete feed silages up to the 60% level, so it acted positively on the qualitative indicators of the silages, modulating the taxonomic communities and allowing the predominance of important groups for the preservation of the silage mass and greater recovery of matter dry. In the fourth experiment, the objective was to evaluate the effect of feeding dairy goats with total ration silage based on forage cactus and buffel grass hay on milk production and composition as well as on the economic indicators of milk production. For the experimental trial, eight crossbred, lactating multiparous dairy goats with 40 ± 2.0 kg of body weight were used. Distributed in a 4x4 double latin square, balanced according to the lactation period. There was a significant difference (P>0.05) regarding milk production and milk fat content. The profitability index was positive only for the diet with 30% inclusion of buffel grass hay, presenting a value of 1.6 R$, while the profitability rate was 60%. Diets with 30% of buffel grass hay promoted an increase in milk production and alterations in the percentage of fat. The simulation to produce 100 dairy goats per year provided revenues higher than production costs, resulting in positive economic indicators for all evaluated scenarios.